Effects of ColdArc welding parameters on the tensile strengths of high strength steel plate investigated using the Taguchi approach - Sabdin, Saiful Din; Hussein, Nur Izan Syahriah; Sued, Mohammad Kamil; Ayob, M.S.; Rahim, M.A.S.A.; Fadzil, Mohd (Universiti Malaysia Pahang, 2019)
The objective of this study is to investigate the effect of process parameters on ColdArc welding of high strength steel plate using 1.2 mm diameter mild steel welding wire. A Taguchi Design of Experiments (DOE) method with grey relational analysis approach was selected for data collection and optimization. 9 experiments were conducted following the L9 (33) Taguchi Orthogonal Array Design. The best result from the experiments for tensile strength was obtained for welding parameters of 70 A (current), 17.6 V (voltage) and 800 mm/min welding speed. Based on the results, the Taguchi analysis predicted the optimised tensile strength would be obtained when the welding current, welding voltage and speed are at 70V, 17.6A and 600 mm/min, respectively. Thus, most significant parameters for tensile properties of cold rolled steel is welding speed (37%), voltage (34 %) and current (28%). These factors are critical in determining the tensile strength, where increasing the welding speed reduces the heat input. However, decreasing the heat input by lowering the welding voltage resulted in bad weld bead formation. © Universiti Malaysia Pahang, Malaysia